Generalization of Self‐Assembly Toward Differently Shaped Colloidal Nanoparticles for Plasmonic Superlattices. Issue 4 (19th February 2023) - Charconnet, Mathias; Korsa, Matiyas Tsegay; Petersen, Søren; Plou, Javier; Hanske, Christoph; Adam, Jost; Seifert, Andreas
Abstract: Periodic superlattices of noble metal nanoparticles have demonstrated superior plasmonic properties compared to randomly distributed plasmonic arrangements due to near‐field coupling and constructive far‐field interference. Here, a chemically driven, templated self‐assembly process of colloidal gold nanoparticles is investigated and optimized, and the technology is extended toward a generalized assembly process for variously shaped particles, such as spheres, rods, and triangles. The process yields periodic superlattices of homogenous nanoparticle clusters on a centimeter scale. Electromagnetically simulated absorption spectra and corresponding experimental extinction measurements demonstrate excellent agreement in the far‐field for all particle types and different lattice periods. The electromagnetic simulations reveal the specific nano‐cluster near‐field behavior, predicting the experimental findings provided by surface‐enhanced Raman scattering measurements. It turns out that periodic arrays of spherical nanoparticles produce higher surface‐enhanced Raman scattering enhancement factors than particles with less symmetry as a result of very well‐defined strong hotspots. Abstract : Periodic superlattices of colloidal metal nanoparticles show excellent plasmonic properties compared to randomly distributed particles. The process of chemically driven, templated self‐assembly is generalized for variously shaped particles, such as spheres, rods, and triangles, yielding regular periodic 2D clusters on centimeter scale with increased enhancement factors for surface‐enhanced Raman spectroscopy.